Spatial Distribution and Change Area of Areas Planted with Summer Crops in the Area of Qushtapa District (2013-2019( - Hashim Hamadamin Hadad; Chiman Omar Abdulrahman (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The research area where qushtapa district sectors have a significant role to play in providing food for some of the area's residents and ensuring food security The chief target of research is to show the distribution and change of the area of planted summer crops on the level of the district's sectors between the years (2013-2019). The research area includes many natural and human characteristics that directly affect the distribution and change of the summer planted area to achieve our goal based on data and statistics from the Qushtapa Agricultural Center for 2013 as of the year Basically , the 2019 data as a comparative year and the result of the change have been shown through several maps and tables that have benefited from the Geographic Information System (Gis) to prepare the maps. As a result, it has been revealed that the summer planted area in the district has decreased by ( -29%) and on the level of 44 sectors the negative change and 11 fractions of the change is positive.